Economic Development and Capital Formation in Burma - Wichmann, Arthur A. (The Review of Economics and Statistics, 1962)
IN this paper it is assumed that the goal of economic development is rising per capita real incomes and that Paul Hoffman's suggested per capita income figure of $300 annually 1 is acceptable as the income level dividing the underdeveloped from the developed economies. It is the purpose in this paper to examine the capital formation rate and the rate of generation of GNP in Burma since I948, the year in which Burma achieved independence. On the basis of Burma's demonstrated economic performance since independence, an endeavor is made to determine the magnitude of the economic development task confronting the Burmese economy. The method employed in this endeavor is one of determining, under varying sets of assumptions concerning aggregate capital-output ratios and population growth rates, the time required to accumulate capital in sufficient amount to provide real per capita incomes of $300 per year.